AST to ALT ratio and risk of hemorrhagic transformation in patients with acute ischemic stroke. (1st November 2020) - Wang, Yanan; Qiu, Ke; Song, Quhong; Cheng, Yajun; Liu, Junfeng; Liu, Ming
ABSTRACT: Background: Hemorrhagic transformation (HT) is a common complication of ischemic stroke. We performed this study to determine whether aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio (AAR) was related to HT, as well as compare the predictive values of AAR, ALT and AST for HT in patients with ischemic stroke. Methods: We included ischemic stroke patients within 7 days of onset. HT was identified by a follow-up imaging examination. Univariate and multivariate logistic regression models were performed to assess the association between AAR and HT. Net reclassification index (NRI) was calculated to assess the ability of AAR, AST and ALT to reclassify risks of HT. Results: A total of 2042 (median age: 69 years; 63.2% males) patients were included in this study, of whom 232 (11.4%) were identified as HT. The receiver-operating characteristic curve analysis showed that the optimal cut-off value for AAR to predict HT was 1.22. Higher AAR (≥1.22) was an independent predictor associated with HT (OR 1.44, 95%CI 1.06–1.97, P = 0.02) after adjusting for covariates. A U-shaped dose–effect relationship was found between AAR level and HT in logistic regression model with restricted cubic splines. In addition, adding AAR to a model containing conventional risk factors significantly improved predictive power for HT (NRI: 15.4%, P = 0.027), but not for ALT (NRI: 10.3%, P = 0.141) or AST (NRI: 8.3%, P = 0.237). Conclusions: Higher AAR was associated with an increased risk of HT after ischemic stroke. In addition, AAR might be a better biomarker for predicting HT than ALT or AST.